Fostering openness in open science: An ethical discussion of risks and benefits - Khalil, Ali Talha; Shinwari, Zabta Khan; Islam, Arshad (Frontiers in Political Science, 2022)
Transformation of science by embracing the concepts of open science presents a very attractive strategy to enhance the reliability of science. Open science policies embody the concepts of open data and open access that encompass sharing of resources, dissemination of ideas, and synergizing the collaborative forums of research. Despite the opportunities in openness, however, there are grave ethical concerns too, and they present a dual-use dilemma. Access to sensitive information is seen as a security risk, and it also possesses other concerns such as confidentiality, privacy, and affordability. There are arguments that open science can be harmful to marginalized groups. Through this study, we aim to discuss the opportunities of open science, as well as the ethical and security aspects, which require further deliberation before full-fledged acceptance in the science community.